Effect of γ-radiation on green onion DNA integrity: Role of ascorbic acid and polyphenols against nucleic acid damage - Jimenez, Liliana Beatriz (2011)
The effect of γ-radiation on green onion DNA integrity, phenol content, oxygen radical absorbance capacity, employing pyrogallol red and fluorescein as probes, as well as ascorbic acid content has been evaluated. Measurements using thiazole orange-DNA fluorescence and agarose gel electrophoresis show that γ-radiation does not lead to an apparent DNA change in green onion. However, it was readily cleaved upon irradiation from the previously isolated nucleic acid. Furthermore, green onion exposure to γ-radiation produces slight increases in the polyphenol concentrations (163-188 μM Trolox eq.) and a decrease in the oxygen radical absorbance using fluorescein (from 245 to 200 Trolox eq.) Interestingly, a high ascorbic acid content (364 μM), which decreases by 40% after γ-ray exposure was measured by using pyrogallol-red-based oxygen radical absorbance capacity induction times from green onion aqueous extracts. Thus, our results suggest that ascorbic acid present in green onion plays a fundamental role in the plant antioxidant response toward γ-radiation exposure, while polyphenols remain largely unchanged, as revealed from oxygen radical absorbance capacity, employing pyrogallol red. © 2011 Elsevier Ltd. All rights reserved.